ORAI FOR PUBLIC SPEAKING : AN AUTOETHNOGRAPHY STUDY - Huda, Muhammad Wafirul (Critical Review of English-Arabic World Journal, 2024)
ABSTRACT The purpose of this study is to train the public speaking and try to overcome the lack of confidence in speaking English by utilizing technology, namely the Orai application. The research method using autoethnography is a research method that is still fairly new to be used in social research. As cited by Anne Shakka (2019), this method is an interesting research method to use because it gives the researcher or writer the opportunity to express himself in the work he produces. The result of this study, showed that I agree that ORAI brings more benefits in learning pronounciation. The researcher was motivated and could learn effectively. . But other than that, there are some problems when using Orai such as, the internet connection must be good. Orai also uses full of English language so sometimes it can be confusing for beginner. Overall, the implementation of ORAI has positive effect for learner in pronouncing correctly and Orai always give feedback to trigger for practicing a lot. On the other hand, pronouncing English well will make a big contribution to communication skills